Riotous assemblies : popular protest in Hanoverian England - Randall, Adrian (Oxford University Press, 2006)
'Riotous Assemblies' examines 18th & early 19th century England through the lens of popular disorder. This book pays particular attention to disturbances in the years between 1795 and 1812, examining how far they indicated the discontinuities discerned by earlier histories of protest.